Village land politics and the legacy of ujamaa. (22nd August 2016) - Greco, Elisa
ABSTRACT: The paper explores the legacies of ujamaa for Tanzanian village land management through the analysis of ethnographic data. The first section considers the ujamaa legacies for Tanzanian village administrative and political institutions and the weight of past top-down politics. In the second section, village land politics are investigated in the light of the reform of the land laws in order then to underline the role of village authorities in collective land claims and to illustrate how village land allocations occur in practice. The third section analyses data from three villages to reflect on the salience of village land politics and Village Land Use Plans. Ujamaa leaves its legacy in the continuity of a potential for democratisation from below resisting the continuity of authoritarianism and centralised decision making from above.